DAKWAH TRANSFORMATIF MELALUI FILANTROPI: FILANTROPI ISLAM DALAM MENGENTAS KEMISKINAN DAN KETIDAKADILAN - Abrori, Abrori; Kharis, Ahmad (Universitas Islam Negeri Ar-Raniry Banda Aceh, 2022)
Abstract: The condition of poverty and injustice that is felt, especially Muslims, will cause sustainable problems, it needs strategic and relevant efforts to unravel the deterioration through da'wah activities. That preaching is not just to spread religion and call for truth. Rather it's about how we can see what we can do for our surroundings. This study aims to know and analyze the potential, role and opportunities of Islamic philanthropy to alleviate poverty and injustice. This type of research is qualitative using descriptive-analytical approach. Data obtained from extracting information through interviews, observations and documentation. The results of the study explained that open transformative da'wah on the problems of poverty and injustice that occur in the community needs to be parsed through Islamic Da'wah. Islamic philanthropy is a manifestation of our love and care as fellow human beings elevates ethical values. The agenda of Islamic Da'wah through zakat, infaq, Sadaqah, and waqaf should be able to parse domestic issues. Effective communication channels, propaganda delivered on target, as well as support from government institutions and institutions, the implementation of Islamic philanthropy relies on solutions to address the problems of poverty and injustice in Indonesia.Keywords: Transformative Da'wah; Injustice; Poverty; Islamic Philanthropy. Abstrak: Kondisi kemiskinan dan ketidakadilan yang dirasakan khususnya umat Islam akan menimbulkan problematika berkelanjutan, maka perlu upaya strategis dan relevan mengurai keterpurukan melalui aktivitas dakwah. Bahwa dakwah bukan sekedar untuk menyebarkan agama dan menyerukan kebenaran. Melainkan dakwah itu tentang bagaimana kita dapat melihat apa yang bisa kita lakukan untuk sekitar kita. Penelitian ini bertujuan mengetahui dan menganalisis potensi, peran dan peluang filantropi Islam mengentaskan kemiskinan dan ketidakadilan. Jenis penelitian ini adalah kualitatif menggunakan pendekatan deskriptif-analitis. Data diperoleh dari penggalian informasi melalui wawancara, observasi dan dokumentasi. Hasil penelitian menjelaskan dakwah transformatif yang terbuka mengenai permasalahan kemiskinan dan ketidakadilan yang terjadi di masyarakat perlu diurai melalui dakwah Islam. Filantropi Islam merupakan wujud cinta dan peduli kita sebagai sesama manusia mengangkat nilai etis. Agenda dakwah Islam melalui zakat, infaq, shadaqah, dan waqaf hendaknya mampu mengurai persoalan domestik. Saluran komunikasi yang terjalin dengan efektif, dakwah yang disampaikan tepat sasaran, serta dukungan dari lembaga dan institusi pemerintahan, implementasi filantropi Islam menyandarkan pada solusi untuk menangani masalah kemiskinan dan ketidakadilan di Indonesia.Kata Kunci: Dakwah Transformatif; Ketidakadilan; Kemiskinan; Filantropi Islam.